Pilot Study of Sequence of Segmental Contributions in the Lower Cervical Spine During Active Extension and Flexion: Healthy Controls Versus Cervical Degenerative Disc Disease Patients. Issue 11 (1st June 2017) - Boselie, Toon F.M.; van Santbrink, Henk; de Bie, Rob A.; van Mameren, Henk
Abstract : Study Design: A retrospective study in which, first, a definition of normal movement in the cervical spine is formulated. Second, use of this definition in differentiating between normal and abnormal movement of the cervical spine is evaluated. Objective: To formulate a clear definition of the normal sequence of segmental contributions in the cervical spine during flexion/extension, and to evaluate the sensitivity, specificity, and reliability of sequence of segmental contributions analysis in differentiating between normal and abnormal movement of the cervical spine in healthy controls and patients with cervical degenerative disc disease (CDDD). Summary of Background Data: To study mobility before and after cervical arthroplasty, segmental range of motion (sROM) is most commonly used. Analysis of sequence of segmental contributions during flexion and/or extension might be more suitable. Methods: The definition was formulated by analyzing flexion cinematographic recordings (FCRs) and extension cinematographic recordings (ECRs) in healthy controls. Sequences in ECRs were more consistent than in FCRs and were therefore used to define "normal" motion. Five blinded spine surgeons scored randomized graphs from ECRs in 20 healthy controls and 10 preoperative CDDD patients, using this definition, at three time points. Sensitivity, specificity, and reliability were calculated. Results: Reliability of scoring as normal or abnormal is high (Fleiss kappa of 0.80–0.84, 95% confidence interval, CI: 0.66–0.98), sensitivity and specificity are also high, with an average sensitivity of 90% (95% CI: 78.4–99.8%), and an average specificity of 85% (95% CI: 72.9–96.4%). Conclusion: This is the first described method that can reliably differentiate between normal or abnormal movement of the cervical spine in an individual subject. This enables an observer to determine if the normal sequence is restored after arthroplasty. In contrast to the given method, sROMs are not able to distinguish between healthy controls and CDDD patients. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the text